Cardiac Fibrosis in the Pressure Overloaded Left and Right Ventricle as a Therapeutic Target - Schimmel, Katharina; Ichimura, Kenzo; Reddy, Sushma; Haddad, Francois; Spiekerkoetter, Edda (Frontiers in Cardiovascular Medicine, 2022)
Myocardial fibrosis is a remodeling process of the extracellular matrix (ECM) following cardiac stress. “Replacement fibrosis” describes the wound healing aspect in the acute phase of injury, such as myocardial infarction. In striking contrast, ECM remodeling following chronic pressure overload insidiously develops over time as “reactive fibrosis” leading to diffuse interstitial and perivascular collagen deposition that continuously perturbs the function of the left (L) or the right ventricle (RV). Examples for pressure-overload conditions resulting in reactive fibrosis in the LV are systemic hypertension or aortic stenosis, whereas pulmonary arterial hypertension or congenital heart disease with right sided obstructive lesions such as pulmonary stenosis result in RV reactive fibrosis. In-depth phenotyping of cardiac fibrosis has made it increasingly clear that both forms, replacement and reactive fibrosis co-exist in various etiologies of heart failure. While the role of fibrosis in RV heart failure pathogenesis needs further assessment, reactive fibrosis in the LV is a pathological hallmark of adverse cardiac remodeling that might drive both development and progression of heart failure (HF). Further, LV reactive fibrosis predicts adverse outcome in various cardiac diseases and contributes to arrhythmias. The ability to effectively block pathological ECM remodeling of the LV is therefore an important medical need. Some studies targeting LV reactive fibrosis have successfully led to improvements of cardiac structure and function in relevant animal models. RV fibrosis is seen as an integral part of RV remodeling and presents at varying degrees in patients with PAH and animal models replicating the disease of RV afterload. The extent to which ECM remodeling impacts RV function and thus patient survival is less clear. We describe differences as well as common characteristics and key players in ECM remodeling of the LV versus the RV following pressure overload. We review pre-clinical studies assessing the effect of anti-fibrotic drug candidates on LV and RV function and their premise for clinical testing. Finally, we discuss the mode of action, safety and efficacy of anti-fibrotic drugs currently tested for the treatment of left HF in clinical trials, which might guide development of new approaches to target right heart failure.